Critical Notes on the Greek Homogenizing National Discourse from the Perspective of the Post-National Discourse - Archakis, Argiris (The Greek Review of Social Research, 2025)
In this paper, I elaborate on specific tools provided by Critical Discourse Studies (CDS) for exposing and critiquing the hypocrisy of the ‘humanitarian/antiracist values’ of the Greek national discourse. In particular, I focus on the interplay between the macro- and micro-levels of discourse and Ι apply Reisigl and Wodak’s (2001) concept of critique to reveal inconsistencies often masked by manipulative hegemonic discourse. I also explore the concept of prospective critique based on alternative, antagonistic discourses aiming to improve communication. Drawing on Fairclough’s (1992) and Laclau and Mouffe’s (1985) frameworks, I examine how antagonism between discourses challenges taken-for-granted assumptions. In this context, I review my research on the asymmetric representation of migrant and majority populations in Greek national discourse. Moreover, I propose post-national discourse as a means of critiquing the Greek national discourse, exposing the constructed and purportedly humanitarian character of its homogeneity and questioning its acceptance. Finally, I argue that this critique can inform educational approaches that destabilize homogeneous worldviews and promote cultural and linguistic hybridity, fostering more equitable interactions between migrant and majority populations.